Perancangan Penerangan Lampu Pada Windsock Berbasis Internet of Things - Willy Seran, Rizhard; Rossydi, Ahmad; Fadhilah Nugrah, Andi (Politeknik Penerbangan Makassar, 2021)
The innovation made by the author of